The Influence of Teachers' Professional and Pedagogical Competence on the Learning Achievement of Junior High School Students in Subrayon 03, Tanggamus Regency - Kholiah, Kholiah; Aswad, Fatqul Hajar; Badrun, M (Lembaga Riset Mutiara Akbar, 2025)
This study aims to analyze the influence of professional and pedagogical competence of teachers on the learning achievement of eighth-grade students at Public Junior High Schools in Subrayon 03, Tanggamus Regency. The research approach used is quantitative with survey methods and multiple linear regression analysis techniques. Data were collected through questionnaires to measure teacher competence and documentation of students' STS scores. The results of the analysis show that simultaneously, professional and pedagogical competence have a significant effect on student learning achievement with an R² value of 0.146. Partially, professional competence has a significant positive effect on student learning achievement (t = 3.405; p less than 0.05), while pedagogical competence also has a significant effect but with a negative coefficient value (t = 2.569; p less than 0.05). These findings indicate that although teacher competence is important in the learning process, its contribution to academic achievement is still limited, and needs to be supported by a more contextual pedagogical approach. This study provides important implications for the development of teacher professionalism as a strategy to improve the quality of education.